Representative Elementary Length to Measure Soil Mass Attenuation Coefficient - J. A. R. Borges; L. F. Pires; J. C. Costa (The Scientific World Journal)
With increasing demand for better yield in agricultural areas, soil physical property representative measurements are more and more essential. Nuclear techniques such as computerized tomography (CT) and gamma-ray attenuation (GAT) have been widely employed with this purpose. The soil mass attenuation coefficient (μs) is an important parameter for CT and GAT analysis. When experimentally determined (μes), the use of suitable sized samples enable to evaluate it precisely, as well as to reduce measurement time and costs. This study investigated the representative elementary length (REL) of sandy and clayey soils for μes measurements. Two radioactive sources were employed (241Am and 137Cs), three collimators (2–4 mm diameters), and 14 thickness (x) samples (2–15 cm). Results indicated ideal thickness intervals of 12–15 and 2–4 cm for the sources 137Cs and 241Am, respectively. The application of such results in representative elementary area (REA) evaluations in clayey soil clods via CT indicated that μes average values obtained for x > 4 cm and source 241Am might induce to the use of samples which are not large enough for soil bulk density evaluations (ρs). As a consequence, ρs might be under- or overestimated, generating inaccurate conclusions about the physical quality of the soil under study.